The coronavirus avian infectious bronchitis virus requires the cell nucleus and host transcriptional factors - Evans, Martin R. (Virology, 1980)
Replication of avian infectious bronchitis virus in permissive BHK-21 cells is blocked when these cells are enucleated or irradiated with ultraviolet light prior to infection, or if cells are treated with α-amanitin during the virus growth cycle. This coronavirus, like influenza virus, can replicate normally in the presence of α-amanitin in Chinese hamster ovary cells which possess a drug-resistant RNA polymerase II. These findings indicate that avian infectious bronchitis virus requires the intact cell nucleus and one or more host transcriptional functions for productive infections. Preliminary data suggest that these cellular functions involve some aspect of virus-directed RNA synthesis.